Caribbean Community : agricultural mechanization policy and strategy formulation : terminal statement (FAO RomeIT, 2000)
Focuses on government policies and strategies affecting agricultural mechanization in CARICOM. Makes recommendations.
Keywords: AGRICULTURAL MECHANIZATION